Identifikasi Viseme Untuk Fonem Bahasa Madura Berbasis Clustering Berdasarkan Facial Landmark Point - Pyepit Rinekso Andriyanto; Joan San; Endang Setyati (J-INTECH ( Journal of Information and Technology), 2023)
The most effective form of language in communicating is spoken or spoken language. When speaking humans will move their mouth and lips to say certain words. This mouth and lip movement model describes a viseme (visual-phonem), namely a group of phonemes that have a visual or almost the same appearance. Madurese language is a unique language and has certain characteristics. In addition to having a language level, Madurese has aspirated phonemes or exhaled word pronunciations such as: /bh/, /dh/, /Dh/, /gh/ and /jh/ which do not exist in other languages. This research discusses the identification of viseme classes for Madurese phonemes based on clustering based on facial landmark points. Of the 47 Madurese language phonemes, 9 Madurese language visemes were obtained from the K-Means clustering process. The clustering process uses feature extraction based on facial landmark points so that the distance calculation for each feature is obtained. The features used are geometric features. The Madurese viseme model is used to build 2D mouth animations in uttering Madurese words or sentences based on input in the form of text. The benefit of this research is for learning purposes in pronouncing Madurese words or sentences, because Madurese has different writing and pronunciation.